Phase transition anomaly observed in PbZrO3/Al2O 3 nanocomposites - Puchmark C. (2017)
Effects of Al 2 O 3 nanoparticle additions on the phase transitions of PbZrO 3 /Al 2 O 3 nanocomposites were investigated. The nanocomposites were prepared by a solid-state reaction method. The phase transition behaviour of the composites was studied by dielectric measurements and differential scanning calorimetry. Nanoparticle additions produced a significant reduction in the temperature of the phase transition from ferroelectric to antiferroelectric phase during the cooling measurement. This resulted in a large thermal hysteresis. The results indicated that the intermediate ferroelectric phase of PbZrO 3 is very sensitive to the Al 2 O 3 impurity. It is proposed that changes in defect chemistry due to the reaction between the nanoparticles and the matrix during sintering are responsible for the anomaly in phase transition behaviour. © 2010 Taylor & Francis.